Smart leadership and its relationship to strategic success: a case study of Palestine Technical College (Palestine Technical College Journal for Research and Studies, 2023)
The study aimed to identify the degree of smart leadership practices and the level of strategic success at Palestine Technical College from the perspective of its employees. The researcher employed the descriptive analytical approach and used a questionnaire as the main instrument for data collection. The questionnaire, in its final form, consisted of (44) items. The study population comprised (189) employees, and (90) questionnaires were successfully retrieved. The comprehensive survey method was adopted, and the questionnaire was administered electronically. The findings revealed that the degree of smart leadership practices was moderate, with a relative weight of (62.96%), while the level of strategic success was also moderate, with a relative weight of (60.98%). Furthermore, the results indicated a statistically significant correlation between the degree of smart leadership practices and the level of strategic success at Palestine Technical College.
Keywords: smart leadership; strategic success; technical colleges